Policing crises and emergencies: conclusions - Cordner, Gary W. (Routledge international handbook of policing crises and emergencies, 2025)
Policing of extreme events and emergencies has not been a mainstream topic in scholarly work on police, nor has it been the focus of most police reform activity, nor does it account for a very big proportion of what most police spend most of their time doing. As the contributions in this handbook have shown, however, when police are called upon to deal with extreme crises, how they perform really matters. At such times, the very fabric of ordinary life is under intense pressure, and many lives are often at stake. For a few hours, days, or months, the public is reminded how much they depend on emergency services, especially police, to protect them from overwhelming threats. While citizens are fleeing from trouble or sheltering in place, police are risking their lives by running toward the danger.